2009
DOI: 10.1677/erc-08-0158
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in mouse tumors induced by Ret-MEN2/FMTC mutations reveals subtype-specific role in survival and interference with immune surveillance

Abstract: Activating mutations in the Ret proto-oncogene are responsible for occurrence of multiple endocrine neoplasia (MEN) type 2A and 2B, and familial medullary thyroid carcinoma (FMTC). A striking genotype-phenotype correlation between the mutated RET codon and clinical manifestation implies that tumorigenesis is conditioned by the type of mutation. We investigated gene expression profiles between and within distinct MEN2 subtypes through whole-genome microarray analysis in tumors induced by NIH-3T3 cells transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Studies have also shown that oncogenic RET can increase proinflammatory mediators, such as IL-6, in thyroid cells and tumors (46)(47)(48). In addition, BRAFV600E has been shown to induce the secretion of IL-6 in melanoma cell lines (24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that oncogenic RET can increase proinflammatory mediators, such as IL-6, in thyroid cells and tumors (46)(47)(48). In addition, BRAFV600E has been shown to induce the secretion of IL-6 in melanoma cell lines (24).…”
Section: Discussionmentioning
confidence: 99%
“…An IHC analysis of these tumors confirmed that granzyme and perforin1 antibodies could stain the immune infiltrate in RET MEN2A-, but not RET MEN2B-induced tumors. Consistently, the authors observed that RET MEN2A/FMTC, but not RET MEN2B tumors expressed CX3CL1/fractalkine, a chemokine involved in the recruitment of cytotoxic immune cells, into both experimental tumor models and in human cancer tissues (Engelmann et al 2009). These data suggest two possible interpretations: 1.…”
Section: Mechanisms Of Immune Surveillance In Mtcmentioning
confidence: 67%
“…RET oncogenic proteins can activate, albeit constitutively and more efficiently, the same signaling pathways induced by physiologically ligand-stimulated RET. However, some differences in downstream signaling between wild-type RET and different MEN2 mutants may account for differential gene expression, that can be translated in differences in tumor microenvironment, and ultimately in disease severity in MTC (Engelmann et al 2009). …”
Section: Type Of Ret Mutation Disease Referencementioning
confidence: 99%
See 1 more Smart Citation
“…5 This causes ligand-independent homodimerization and constitutive autophosphorylation, and activation of the RET kinase, leading to the stimulation of a complex network of signal transduction pathways that contribute to dysregulated growth and survival. 7,8 Activated oncogenes such as RET are highly attractive targets for the development of anticancer agents. 9 Principles of RET inhibition in MTC cells include molecular strategies to interfere with its kinase activity by small molecules [10][11][12] and receptor dimerization using aptamers or soluble RET ectodomain.…”
Section: Introductionmentioning
confidence: 99%